Host interferon-γ inducible protein contributes to Brucella survival - Ritchie, Jennifer; Rupper, Adam; Cardelli, James; Bellaire, Bryan (Frontiers in Cellular and Infection Microbiology, 2012)
Brucella spp. are highly adapted intracellular pathogens of mammals that cause chronic infections while surving and replicating in host monocytes and macrophages. Although monocytes are normally susceptible to infection, pretreatment with pro-inflammatory cytokine interferon- (IFN-) activates cellular defense mechanisms that increase intracellular killing of Brucella and prevents bacterial replication. We examined the contribution of the IFN- inducible GTPase, LRG-47, to B. abortus 2308 infection in in vitro and in vivo murine models. Infecting nonactivated macrophages from LRG-47-/- mice revealed that loss of this host protein negatively effected the intracellular survival and replication of IgG opsonized B. abortus. In contrast, survival and replication of non-opsonized B. abortus was the same in both C57/B6 and LRG-47-/- peritoneal macrophages. Following IFN-γ activation of LRG-47-/- monocytes, IgG opsonized B. abortus survived better than non-opsonized bacteria. Similar experiments using macrophages from BALB/c and C57/B6 mice found no difference in intracellular survival or replication between non-opsonized and IgG opsonized B. abortus in either resting or IFN-γ activated monocytes. The differential fate of opsonized and non-opsonized B. abortus was only observed in macrophages collected from LRG-47-/- mice. Given the specific nature of the relationship between this host protein and the mechanism of Brucella internalization, LRG-47-/- mice were infected with B. abortus to assess whether the loss of the lrg47 protein would affect the ability of the bacteria to colonize or persist within the host. B. abortus were able to establish and maintain similar numbers of bacteria in both C57/B6 mice and LRG-47-/- through 3 weeks post intraperitoneal infection. By nine weeks p.i. fewer B. abortus were recovered from LRG-47-/- mice than controls, suggesting that the host protein has a positive role in maintaining long term persistence of the bacteria within the host.